DEVELOPMENT OF MARKETING STRATGIES FOR HANDBAG MADE FROM VETIVER GRASS UNDER THE BURAWA BRAND - Krankum, Kantapon; Fugfang , Tuchanon; Thammarit, Thanakorn; Hirankitti, Pimpa; Buaprommee , Nathamon; Mechinda, Panisa (RMUTT Global Business and Economics Review, 2021)
The objectives of this research were as follows: (1) to examine the attitude toward marketing mixes in terms of product, brand, price, distribution, advertising and the purchase intention of Burawa bag; (2) to investigate those attitudes and the purchase intention as categorized by demographic characteristics; and (3) to explore the relationship between the attitude toward marketing mixes and the purchase intention. The online questionnaires were used as data collection instrument from a total sample size of 635. Statistical methods used were One-sample t-test, Independent Samples t-test, One-way ANOVA and Pearson correlation. The results indicated that most of respondents were female, aged between 24-39 years old (Gen Y). Their monthly household income were 35,000 Baht or less. They had bachelor’s degree. Most of them were students, company employees and government officers. The significant results of hypothesis testing were as the following. (1) The mean value of marketing mixes were above 3.41 in every aspects except for the brand name recognition and the purchase intention. (2) Age difference resulted in attitudinal differences toward the product and distribution channel. That is, Gen Y had attitude toward distribution channel via Facebook higher than other Gen Groups. Gen B had better perception of brand recognition than other Gen Groups. (3) Consumers having monthly household income less than 35,000 Baht or equivalent agreed with advertising and selling via Facebook. (4) In terms of educational level, attractive information provided on Facebook and brand reputation influenced the attitude of those who had no bachelor’s degree. (5) Gender differences didn’t affect any differences in attitude. (6) with regards to marketing mixes, price, brand reputation and the colorfulness of bag had association with the purchase intention.